Pengaruh Penggunaan Media Pembelajaran dengan Software Prezi Terhadap Minat Belajar Matematika Siswa - Alviyaturrohmah Alviyaturrohmah; Saluky Saluky; Arif Muchyidin (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2017)
The use of media in learning activity can be a solution for teachers to overcome the problems that arise in learning. One of the problem is learning interest. It is important for teachers to cultivate students' learning interests. One of the media that can be used in learning is learning media with Prezi software. Learning media with Prezi software can be inserted with images, videos, music that can stimulate students' interest in learning. Population in this research is all class VIII SMP Negeri 4 Palimanan Kabupaten Cirebon while sampling using cluster random sampling technique and elected class VIII E as experiment class. Based on the results of the data obtained; the results of questionnaire analysis of students' responses to learning mathematics using Prezi software showed strong criteria with an average of 71% and the results of student interest in mathematics questionnaire analysis also showed strong criteria with an average of 80%. Based on the results of the hypothesis, it can be seen that the value of thitung > t_tabel, that is 4.546> 1.7011. Because t_hitung> t_tabel, then the decision to be taken is to reject H0 and accept Ha, it means that the hypothesis is accepted. The writer takes the conclusion that there is significant influence between learning media with Prezi software to the students' learning interest in mathematics.